2012
DOI: 10.7203/relieve.18.2.2001
|View full text |Cite
|
Sign up to set email alerts
|

Learning strategies in excellent and average university students. Their evolution over the first year of the career

Abstract: The aim of this paper was to analyze the evolution of learning strategies of two groups of students, excellent and average, from 11 degrees of the UPV (Valencia/Spain) in their freshman year. We used the CEVEAPEU questionnaire. The results confirmed the availability of better strategies of excellent students and also the existence of evolutionary patterns in which affective-emotional strategies decrease, such as value of the task or internal attributions, and that others increase, such as extrinsic motivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…Research had already highlighted this issue (Camarero et al, 2000;Gargallo, 2006) and further investigation should include other degree programs to confirm this pattern. Finally, as Gargallo (2012) and Salazar & Heredia (2019) had already pointed out, the use of learning strategies evolves throughout the years. The present study showed greater use of learning strategies by second-year students compared to first-year students.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Research had already highlighted this issue (Camarero et al, 2000;Gargallo, 2006) and further investigation should include other degree programs to confirm this pattern. Finally, as Gargallo (2012) and Salazar & Heredia (2019) had already pointed out, the use of learning strategies evolves throughout the years. The present study showed greater use of learning strategies by second-year students compared to first-year students.…”
Section: Discussionmentioning
confidence: 83%
“…For instance, Gargallo (2006) and Juárez et al (2016) concluded that students with higher academic performance use more learning strategies, especially those related to information search, selection and processing, and metacognitive and context control strategies. Likewise, research has shown that students enrolled in different degree programs seem to use different learning strategies (Camarero et al, 2000;Gargallo, 2006) and they use more effective strategies throughout the years of study (Camarero et al, 2000;Gargallo, Almerich, Suárez-Rodríguez, & García-Félix, 2012). Other studies have found differences in the strategic learning of male and female students (Ghiasvand, 2010;Rossi Casé et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the findings suggest that promoting or intervening to improve the strategic profile of university students should focus, above all, on meta-cognitive strategies and those related to awareness and regulation of the affective components involved in learning processes, since these are the ones students report lower usage of. In fact, previous studies have consistently established that meta-cognitive strategies have a positive and significant effect on academic performance (Camarero et al, 2000;Cano & Justicia, 1993;Gargallo, Almerich, Suárez-Rodríguez, & García-Félix, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…En este sentido, los hallazgos sugieren que para promover o intervenir en la mejora del perfil estratégico de los estudiantes universitarios debe incidirse, sobre todo, en las estrategias meta-cognitivas y las relacionadas con el conocimiento y la regulación de los componentes afectivos implicados en el proceso de aprendizaje, dado que éstas son las que relativamente en menor medida dice utilizar el alumnado. De hecho, estudios previos han establecido de forma consistente que las estrategias meta-cognitivas influyen de forma positiva y significativa en el rendimiento académico (Camarero et al, 2000;Cano & Justicia, 1993;Gargallo, Almerich, Suárez-Rodríguez, & García-Félix, 2012).…”
Section: Conclusionesunclassified
“…Psychology examines learning by analysing variables such as academic motivation, self-efficacy, learning strategies, learning approaches and learning styles (Çetin, 2015; Gargallo et al ., 2012; Illahi and Khandai, 2015; McLaughlin and Durrant, 2016; Pérez et al ., 2013; Pexoto et al ., 2012; Rodríguez et al , 2019; Warden and Myers, 2017). This study addresses the matter of learning styles.…”
Section: Introductionmentioning
confidence: 99%